Creativity as social critique: a case study of the opera Have a Good Day! - Paltanavičiūtė, Justina (Creativity Studies, 2022)
The article explores the communication of social critique in contemporary art. The article aims to reveal the connections between art and politics existing in the theory of art aesthetics and art practice. Empirical research: the content analysis of critical reviews allowed to determine that the pronouncements of the authors and the official agenda presentation of a work of art that potentially articulates a political message but is considered hermetic affect and indicate the direction of reception. An example of contemporary opera was deliberately chosen for the research. Contemporary opera is often considered as a hermetic domain of creativity, solving only aesthetic, but not sociopolitical challenges. However, from the very first examples, the opera genre has been treated as an improvised and aestheticized public sphere, enabling to communicate ideology principles of the dominant political power or, conversely, to demonstrate social criticism to those in power. Opera research that focuses on political aspects is usually based on the musicological paradigm conducted on the basis of analysis of aesthetic regime -opera as a work of art communicating a socio-political message is still rarely explored. However, contemporary artists often creatively rely on politically active narratives and themes. This enables the opera genre to be seen as a platform for political communication.